Brain Volumetric Alterations in Preclinical HIV-Associated Neurocognitive Disorder Using Automatic Brain Quantification and Segmentation Tool - Li, Ruili; Qi, Yu; Shi, Lin; Wang, Wei; Zhang, Aidong; Luo, Yishan; Kung, Wing Kit; Jiao, Zengxin; Liu, Guangxue; Li, Hongjun; Zhang, Longjiang (Frontiers in Neuroscience, 2021)
Purpose: This study aimed to determine if people living with HIV (PLWH) in preclinical HIV associated neurocognitive disorder (HAND), with no clinical symptoms and without decreased daily functioning, suffer from brain volumetric alterations and its patterns. Method: Sixty PLWH at the HAND preclinical stage were evaluated, including 19 subjects with asymptomatic neurocognitive impairment (ANI), 17 subjects with cognitive abnormality not reach ANI (Not reach ANI), and 24 subjects with cognitive integrity. Moreover, 25 healthy volunteers were set as the seronegative normal controls (NC). These individuals underwent sagittal three-dimensional T1-weighted imaging (3D T1WI). Quantified data and volumetric measures of brain structures were automatically segmented and extracted using AccuBrain®. In addition, the volumes of brain structures that showed significant differences between preclinical HAND and NC were correlated with cognitive/clinical variables by using Spearman or Pearson correlation analysis. Results: The significant difference was shown in the relative volumes of ventricular system, bilateral lateral ventricle, thalamus, caudate, and left parietal lobe gray matter between the preclinical HAND and NC. Furthermore, the relative volumes of bilateral thalamus in preclinical HAND were negatively correlated with attention/working memory (left: r= -0.313, p=0.015; right: r= -0.266, p=0.040), and there was a negative correlation between the disease course and left parietal lobe gray matter (r= -0.359, p=0.005). No significant difference was found among preclinical HAND subgroups in all indices, and the difference between the individual groups (Not reach ANI and Cognitive integrity group) and NC was also insignificant. However, there was a significant difference between ANI and NC in the relative volumes of bilateral caudate and lateral ventricle. Conclusions: PLWH at the HAND preclinical stage suffer from brain volumetric alterations. AccuBrain® provides potential value in evaluating HIV-related neurocognitive dysfunction.